Product development of a plastic transport structure - Polus, Sarmad (My University, 2010)
This work was performed in cooperation between Chalmers University of Technology and Supply Chain and Packaging Concepts at IKEA in Sweden, focusing on the development of a load carrying product called Load Protection Panel. The work dealt with dimensions and choice of material, which are restricted by the compatibility with various equipments and prevailing environmental condition within the supply chain of IKEA. The study was based on two methodologies from Industrial Design Engineering and Advanced Engineering Materials, combining a methodology for assessing requirements and performing the development process with understanding materials character and assessing material properties. The first task was to study the complex supply chain by conducting field observations in combination with semi-structural interviews with users of this product. The results combined with a functional and cause analysis provided a basis for a detailed requirement specification, expressing the identified needs. The specification was extended by including critical material properties. The material study indicated recycled PET and virgin PP as the two interesting alternative materials. Recycled PET was mechanically characterized in order to investigate the difference between the recycled material and the virgin one. Measured properties were used in a finite element analysis (FEA) of the mechanical behavior of the conceptual design, mainly simulations of the critical stresses for LPP made of both PP and recycled PET. Two new concepts were then generated based on feedback from IKEA with some new requirements and changes of the importance levels of some existing requirements. The most important improvement needed was an increase of the load carrying capacity if using both recycled PET and PP as. Consequently, a parametric redesign resulted in a new design, used for further encouraging finite element method simulation. An improvement in the load capacity was simulated, which resulted in new concepts combining both new design and using PP and recycled PET. The final concepts were evaluated by means of their expected ability to meet the adjusted requirement specification. The new design with reduced overall thickness is recommended for the HM, with a reservation for the processability that needs to be verified by a mold designer. For the final material choice between virgin PP and recycled PET, it is pointed out that PET provides relatively good mechanical property but with a more challenging processability compared to PP, and that PP provides important benefits such as a lower density and the integration of corner protections when secured with plastic straps. For final selection of material, it still remains to evaluate prototypes, particularly regarding the creep resistance and the possibility to reuse.
Keywords: Hållbar utveckling; Produktion; Övrig teknisk materialvetenskap; Sustainable Development; Production; Other materials science